(untitled) (Comparative & International Education Series, 2021)
The chapter provides an understanding of the ways COVID-19 is affecting higher education and advances practical strategies for managing the challenges caused by the pandemic. To understand the effect of the COVID-19 pandemic on higher education, it is prudent to understand the context within which the institutions of higher learning operate. It also offers an overview of the education system in Kenya, followed by a situation analysis. It then explores how COVID-19 is affecting and shaping the future of higher education and based on literature, presents the strategies to manage the effects of the pandemic. How to cite: Wekullo, C. S., Shiundu, J. O., Ouda, J. B., & Mutevane, A. (2022). COVID-19 crisis and the future of higher education: Perspectives from Kenya. In J. S. McKeown, K. Bista, & R. Y. Chan (Eds.), Global higher education during COVID-19: Policy, society, and technology (pp. 73-92). STAR Scholars. https://starscholars.org/product/global-education/